Material Problems in Civil Engineering: Ideas-Driving Forces-Research Arena. (2015) - Czarnecki, Lech; Hager, Izabela; Tracz, Tomasz
Abstract: The paper presents the evolution of the MATBUD conference and discusses the driving forces of research in the field of building materials. The paper attempts to interpret the trends in relation to the development of building material engineering. The approach adopted here is the investigation of the relation between material model and performance model as well as main drivers of building material research: idea, performance, research tools development, application and technological evolution.